Identification of Nucleoside Analogs as Inducers of Neuronal Differentiation in a Human Reporter Cell Line and Adult Stem Cells. (12th January 2015) - Raasch, Katharina; Malecki, Edith; Siemann, Maria; Martinez, Malayko M.; Heinisch, Jürgen J.; Müller, Janine; Bakota, Lidia; Kaltschmidt, Christian; Kaltschmidt, Barbara; Rosemeyer, Helmut; Brandt, Roland
<x xml:space="preserve">Abstract</x> Nucleoside analogs (NSAs) were among the first chemotherapeutic agents and could also be useful for the manipulation of cell fate. To investigate the potential of NSAs for the induction of neuronal differentiation, we developed a novel phenotypic assay based on a human neuron‐committed teratocarcinoma cell line (NT2) as a model for neuronal progenitors and constructed a NT2‐based reporter cell line that expressed eGFP under the control of a neuron‐specific promoter. We tested 38 structurally related NSAs and determined their activity to induce neuronal differentiation by immunocytochemistry of neuronal marker proteins, live cell imaging, fluorometric detection and immunoblot analysis. We identified twelve NSAs, which induced neuronal differentiation to different extents. NSAs with highest activity carried a halogen substituent at their pyrimidine nucleobase and an unmodified or 2′‐O‐methyl substituted 2‐deoxy‐β‐D‐ribofuranosyl residue as glyconic moiety. Cladribine, a purine nucleoside with similar structural features and in use to treat leukemia and multiple sclerosis, induced also differentiation of adult human neural crest‐derived stem cells. Our results suggest that NSAs could be useful for the manipulation of neuronal cell fate in cell replacement therapy or treatment of neurodegenerative disorders. The data on the structure and function relationship will help to design compounds with increased activity and low toxicity.